Forecasts And Environmental Decision Making : The Content And Predictive Accuracy Of Environmental Impact Statements /: The Content And Predictive Accuracy Of Environmental Impact Statements. (2018) - Culhane, Paul J; Friesema, H. Paul, 1936-2013; Beecher, Janice A
No abstract available